2020
DOI: 10.1016/j.rmcr.2020.101318
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with methyl-prednisolone pulses for the late phase of COVID-19 with respiratory failure: A single-center case series

Abstract: Although some prospective studies provided the evidence of corticosteroids for critically ill patients with COVID-19, the optimal dosage or timing of corticosteroids is still unknown. This is a case series of four patients on methyl-prednisolone pulses for the late phase of Coronavirus disease 2019 (COVID-19) with respiratory failure in our hospital. All patients needed invasive mechanical ventilation and had bimodal worseness of their respiratory status with consolidation and volume loss after intubation. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…10 The scales gradually tipped in the other direction thanks to the realization that SARS-CoV-2 may produce lung damage by igniting a destructive immune response in that organ rather than through direct viral cytopathic effects 11 and the corollary that viral persistence may not be the driver of progressive 17) 60 ( 16) 66 ( 13 (Continues) lung disease in SARS-CoV-2. 12 Once RCTs evaluating corticosteroid therapy were launched, the dosing regimens resembled those of favorable prior studies of early corticosteroid administration in mixed ARDS populations: for example, methylprednisolone 1 mg/kg/day in the trial by Meduri et al 13 and dexamethasone 20 mg once daily followed by 10 mg once daily in the trial by Villar et al 14 The belief in some circles that COVID-19 pneumonia differs from routine ARDS in the degree of maladaptive exaggeration of the lung immune response led to sporadic reports [15][16][17][18] of the use of corticosteroids at pulse dose of 1 gm/day for at least 2 days as defined in the present study and as might be done for immune-mediated lung diseases such as pulmonary vasculitis or primary lung allograft dysfunction. Administration of corticosteroids at this magnitude has not been studied systematically in any COVID-19 pneumonia population before the present study.…”
Section: Discussionmentioning
confidence: 99%
“…10 The scales gradually tipped in the other direction thanks to the realization that SARS-CoV-2 may produce lung damage by igniting a destructive immune response in that organ rather than through direct viral cytopathic effects 11 and the corollary that viral persistence may not be the driver of progressive 17) 60 ( 16) 66 ( 13 (Continues) lung disease in SARS-CoV-2. 12 Once RCTs evaluating corticosteroid therapy were launched, the dosing regimens resembled those of favorable prior studies of early corticosteroid administration in mixed ARDS populations: for example, methylprednisolone 1 mg/kg/day in the trial by Meduri et al 13 and dexamethasone 20 mg once daily followed by 10 mg once daily in the trial by Villar et al 14 The belief in some circles that COVID-19 pneumonia differs from routine ARDS in the degree of maladaptive exaggeration of the lung immune response led to sporadic reports [15][16][17][18] of the use of corticosteroids at pulse dose of 1 gm/day for at least 2 days as defined in the present study and as might be done for immune-mediated lung diseases such as pulmonary vasculitis or primary lung allograft dysfunction. Administration of corticosteroids at this magnitude has not been studied systematically in any COVID-19 pneumonia population before the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Thereupon, we started pulse steroid therapy, which has been shown to be beneficial for the late phase of COVID-19 with respiratory failure. 10 Since hypoxia did not improve, pirfenidone was initiated with the decision of the council.…”
Section: Discussionmentioning
confidence: 99%
“…Edalatifard et al reported that 250 mg/day steroid pulse therapy for 3 days resulted in a significantly higher clinical improvement and a lower mortality rate than the control group [ 17 ]. In a report from Japan, Tamura et al reported the therapeutic effect of high-dose steroid pulse therapy (1 g of methylprednisolone (mPSL) for 3 days) [ 18 ]. Furthermore, Pinzon et al reported that high-dose methylprednisolone for 3 days followed by oral prednisone for 14 days reduced recovery time and the need for intensive care compared to 6 mg dexamethasone for 7–10 days [ 19 ].…”
Section: Discussionmentioning
confidence: 99%